Effects of arabinoxylan and chlorogenic acid on the intestinal microbiota in dextran sulfate sodium–treated mice - Xie, Minhao; Zhang, Xianzhu; Wang, Xiaoxiao; Chen, Guijie; Liu, Jianhui; Zeng, Xiaoxiong; Yang, Wenjian (Frontiers in Nutrition, 2022)
Dietary non-starch polysaccharides and phenolics are usually ingested at the same time. They are both regarded as prebiotics, and they regulate the intestinal microbiota through various mechanisms. Notably, however, reports of their combined or synergistic effects are rare. Arabinoxylan (AX), a polysaccharide, and chlorogenic acid (CA), a polyphenol, are widely consumed, and their effects on the microbiota have previously been discussed. In the present study, they were given to dextran sulfate sodium (DSS)–treated mice, separately and together, and the intestinal microbiota were investigated by high-throughput sequencing. The data showed that CA attenuated body weight loss, colon shortening, and histological damage in DSS-treated mice, while neither AX nor the AX+CA combination exhibited any ameliorating potential. AX+CA had less of a modulating effect on intestinal microbiota profiles than did CA. AX+CA administration increased the relative abundance of Flavonifractor, Coprobacillus, and Clostridium_XlVa, and decreased the abundance of Robinsoniella and Lactobacillus. Compared to AX and CA, AX+CA contributed to a more complicated shift in the biological functions of the intestinal microbiotaAX seemed to weaken the beneficial effects of CA, at least in the present experimental model of DSS-induced colitis. The combined effects and mechanisms of dietary polysaccharides and phenolic compounds on the intestinal microbiota and on overall health still need to be further investigated.